Gerenciamento de projetos no contexto de organização de uma feira de ciências - (:unkn) unknown (Universidade Federal do Pampa, 2022)
This work presents a case of exploratory study about Unipampa’s XI Feira de Ciencias from Campus Bagé developed in 2022. The general objective of this research was the applyment and the analyzes of how the knowledge and techniques used in projects’ management can contribute to better disseminating Science and Technology in the Campanha/Fecipampa Region – Pampa’s Science Fair. For this, the Project Management Body of Knowledge (PMBOK Guide, 2017) works as a theoretical reference providing a knowledge base on project management and helping on the understanding of quality, resources, communication and other competencies on the same project. The following specific objectives were outlined: i) a literature review on the topic of science fair to learn about what Brazilian dissertations and theses have already discussed on the proposed research topic; ii) the identification of the stages and the mapping of the process of elaboration and execution of a science fair; iii) and the development and investigation of the usage of an organizational chart with an organizing committee and subcommittees for communication, registration and certification, evaluation and infrastructure. In addition, we propose a flowchart with all the activities that must be developed by the team of Science Fair of Campus Bagé. The research is characterized as qualitative and the method of the single case study was adopted based on Yin's theory. Assessment questionnaires and group interviews were used as tools for data production. The subjects participating in the research were the professors who supervised the student´s projects that were part of the XI Science Fair, the project execution team and scholarship students who collaborated in the development of the fair's organization activities. As a result of this study, we present the guiding proposition: The integration between the project's subcommittees contributes to the overcoming points negatively evaluated by the student´s projects supervisors and potentiates team's sense of belonging. In addition, we indicate, through a flowchart, all the activities to be developed during the organization of a science fair and show the interconnections between the subcommittees. It was also possible to know the opinion of the professors (student´s projects supervisors) and the team about the organization of the XI Science Fair of Campus Bagé. These data provided important information and helped to indicate some negative points that require attention in future studies.
Keywords: Feira de Ciências; Gerenciamento de projetos; Planejamento; Gestão; Science Fair; Management of projects; Planning; Management; CNPQ::CIENCIAS SOCIAIS APLICADAS